The Relationship Between Knowledge Of The Dangers Of Smoking And Stress Levels In Adolescent Boys At SMK Negeri 3 Medan In 2023 - Pase, Muslimah (Sean Institute, 2024)
Stress is a normal reaction, so everyone will experience it, both adults, teenagers, and even children. The stress used by each individual varies, among others, with vacations, meditation, yoga and smoking. Smoking is one example of an ineffective but widely favored management strategy. According to World Health Organization (WHO) data, it is found that every 6 seconds there is one death caused by tobacco worldwide. This study aims to determine whether there is a relationship between knowledge of the dangers of smoking and stress levels in male adolescents at SMK Negeri 3 Medan in 2023. The research design is a quantitative study using a correlation description, with cross sectional. the population in this study were male students with a total of 351 people. The sampling technique in this study used a purposive sampling technique with the slovin formula by fulfilling the inclusion criteria, namely 78 people. Methods of data collection using a questionnaire. The statistical test used is the Spearman Rho with an α value of 0.05. The results of the research on the knowledge of the dangers of smoking, that the majority of the dangers of smoking are the majority are not good, amounting to 62 people (79.5%), the stress level is the majority of the weight, amounting to 62 people (79.5%). stress level with a p-value of 0.000 (<0.05). The conclusion of the study shows that there is a relationship between knowledge of the dangers of smoking and stress levels in adolescent boys at SMK Negeri 3 Medan in 2023. It is hoped that respondents will be educated about the importance of increasing knowledge of the dangers of smoking by reducing stress levels, especially for students at school.